Analisis Perbaikan Proses Bisnis menggunakan Quality Evaluation Factor (QEF) dan Root Cause Analysis (RCA) pada Baraya Cargo - Muhammad Rasyad Fauzan; Nanang Yudi Setiawan; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Baraya Cargo is a shipping company that carries out shipping activities through a series of business process activities starting from contract agreements, shipping preparation, delivery, and ending with the issuance of invoices. The current business processes are still experiencing problems from time delays and the occurrence of a lack of documents that disrupt the performance of Baraya Cargo. Therefore, improvement activities were carried out starting from modeling the main business processes in the form of Business Process Model and Notation (BPMN) in the Bizagi application. The business process model is then evaluated using the Quality Evaluation Framework (QEF). It was found that there are 3 main business processes that have problems where there are inappropriate metric values. After that, an analysis was carried out using Root Cause Analysis (RCA) to find the root cause of the metrics that did not match. Recommendations are then given using streaming tools from Business Process Improvement (BPI). Finally, a simulation was carried out through the Bizagi application to determine the time performance improvement between business processes (as-is) and business processes (to-be). The simulation results show that the contract agreement business process has increased performance by 75.5%, the delivery business process is 1.6% and the invoice issuance business process is 76.5%. It can be seen that the implementation of the recommended business process shows a significant performance improvement when applied to Baraya Cargo.